Prozdrowotne właściwości rodzimego miodu zwerbalizowane w wybranych opracowaniach pszczelarskich i apiterapeutycznych = Health-promoting properties of native honey verbalised in selected beekeeping and apitherapeutic studies - Węgorowska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Honey and health are two nouns and also concepts that have permanently become part of the history of mankind. The qualities of the bee honey have been known since ancient times, and the apitherapy that is associated with it is currently being revived. The objective of the present linguocultural considerations is, this time, to present the advantages of various varieties of Polish honey verbalised in selected, both specialist and popular science publications in the field of beekeeping and apitherapy. The beneficial values of this natural biopreparation, expressed in words, make us aware of the axiologically characterised benefits offered to us by the surrounding flora and fauna.
Keywords: miód; zdrowie; walory prozdrowotne; werbalizacja; lingwokulturologia; honey; health; health-promoting qualities; verbalization; linguoculturology